Penetapan Imbalan dalam Sistem Samsarah pada Praktik Jual Beli Sapi Tinjauan Ekonomi Islam - Linafsi, Muzahadatul; Hasanah, Niswatun; M. Shaiful Umam (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2025)
This study aims to analyze the implementation of the samsarah system in the practice of buying and selling cattle in Petiyin Hamlet, Wadeng Village, Sidayu Subdistrict, Gresik Regency, and review the determination of compensation from an Islamic economic perspective. This research uses a qualitative approach with a field research method to explore data in depth. The results showed that the samsarah system facilitates cooperation between farmers, brokers, and buyers, with the brokers acting as liaisons. The determination of the reward is often based on the sincerity of the cattle owner after the sale, usually half of the profit from the sale of the cattle, although it is in line with sharia principles, but transparency and certainty need to be improved. This practice is generally in line with Islamic economic principles that emphasize justice, moral responsibility, and transparency, and does not contain elements of usury or gharar. This study concludes that the samsarah system has the potential to continue to be developed by paying attention to the principles of Islamic economics to make it more fair and transparent.